Reactive Oxygen Species and Metabolism in Leukemia: A Dangerous Liaison - Romo-González, Marta; Ijurko, Carla; Hernández-Hernández, Ángel (Frontiers in Immunology, 2022)
Reactive oxygen species (ROS), previously considered toxic by-products of aerobic metabolism, are increasingly recognized as regulators of cellular signaling. Keeping ROS levels low is essential to safeguard the self-renewal capacity of hematopoietic stem cells (HSC). HSC reside in a hypoxic environment and have been shown to be highly dependent on the glycolytic pathway to meet their energy requirements. However, when the differentiation machinery is activated, there is an essential enhancement of ROS together with a metabolic shift toward oxidative metabolism. Initiating and sustaining leukemia depend on the activity of leukemic stem cells (LSC). LSC also show low ROS levels, but unlike HSC, LSC rely on oxygen to meet their metabolic energetic requirements through mitochondrial respiration. In contrast, leukemic blasts show high ROS levels and great metabolic plasticity, both of which seem to sustain their invasiveness. Oxidative stress and metabolism rewiring are recognized as hallmarks of cancer that are intimately intermingled. Here we present a detailed overview of these two features, sustained at different levels, that support a two-way relationship in leukemia. Modifying ROS levels and targeting metabolism are interesting therapeutic approaches. Therefore, we provide the most recent evidence on the modulation of oxidative stress and metabolism as a suitable anti-leukemic approach.